Hubungan antara Penerimaan Diri dan Depresi pada Komunitas Gay di Surakarta - Pratiwi, Niken Ayu; Suwito, Djoko; Hikmayani, Nur Hafidha (Nexus Kedokteran Komunitas, 2014)
Background: Gay is one of high-risk groups to have depression. The prevalence of depression in gay is reportedly higher than that in heterosexual people. Gay is often faced to low self-acceptance or social-acceptance problems which potentially lead to depression. This study aimed to seek the correlation between self-acceptance and depression in gay community. Methods: This was an analytical study using cross sectional approach, conducted in May 2013 at Gessang Foundation in Surakarta. Samples were purposively selected based on inclusion and exclusion criteria. Subjects were asked to fill in: (1) biodata and informed consent forms, (2) the L-MMPI questionnaire to evaluate respondentsâ truthfulness in answering questionnaires, (3) the Bergerâs Self-Acceptance Scale questionnaire to measure self-acceptance scores, and (4) the Beckâs Depression Inventory Scale to measure depression scores. Samples were excluded when either declined at least 10 statements from the L-MMPI questionnaire, did not completely fill in the forms and questionnaires, had chronic diseases, or were on long-term medications. Data were analyzed by Pearsonâs Product Moment correlation test using SPSS 20.0 for Windows. Results: The self-acceptance of 31 subjects eligible for this study was relatively low (mean score = 104.6). The overall mean of depression scores was 14.7 and only 6 subjects (19.4%) were not having depression as they scored less than 10. The analysisÂ  showed a Pearsonâs correlation coefficient (r) of -0.758 (p<0.001), suggesting that self-acceptance and depression were significantly negatively correlated. Conclusion: There was a strong and statistically significant negative correlation between self-acceptance and depression at a gay community in Surakarta. Keywords: Self-acceptance, Depression, Gay